Drug-Induced Liver Injury Used in the Treatment of Inflammatory Bowel Disease. (19th January 2022) - Núñez F, Paulina; Quera, Rodrigo; Bay, Constanza; Castro, Fabiola; Mezzano, Gabriel
Abstract: Therapeutic options for the management of inflammatory bowel disease [IBD] have been expanding in recent decades. New biological and small molecule therapies have been incorporated into the pharmacological arsenal, allowing a more personalized management, and seeking increasingly strict remission goals. However, the fear of developing adverse events represents one of the most important limitations in deciding its use by patients and by a multidisciplinary team. Despite the risk of hepatotoxicity of thiopurines and methotrexate, these drugs are still used either as monotherapy or as combined therapy with anti-tumour necrosis factor [anti-TNF] biological agents. Although drug-induced liver injury [DILI] appears to be less frequent with anti-TNF agents, newer biologics and small molecules, liver tests should be considered in the follow-up of these patients, especially regarding future combined therapy of biologics or of these drugs with small molecules. The objective of this review is to show data on the risk of developing DILI in patients with IBD who are undergoing treatment with traditional therapy or new drugs, whether biological or small molecules.